Improvement of Physical, Honesty, Discipline and Cooperation in Class IV Elementary School Students through Circuit Training Learning Model - Dean Novianti; I Made Sriundy Mahardika; Abdul Rachman Tuasikal (BIRCU, 2020)
Physical education program for sport and health allocates four lesson hour of which each hour consists of 35 minutes in one week. It requires an innovative and efficient learning model in order to improve physical fitness, honesty, discipline, and cooperation. The researcher developes a circuit training learning model in the from circuit games which is a modified form of circuit training. The study aim to examine the effectiveness of the circuit training learning model in improving physical fitness, honesty, discipline, and cooperation in students of Elementary School Sidoarjo. The type of research used is quantitative and qualitative by using research and development method, and data analysis using ANOVA. The data collection process is carried out by pre-test and post-test and then the results of the research data are analyzed using SPSS series 2.0. The results of the study shows (1) the sig value of 0,011 smaller than the 0,05 ( p< 0,05 ), meaning that there is the difference in the results of the TKJ I test on groups of students who are not treated compared to the group of students who are given the learning model. (2) the average group of students who are not given the treatment (control group) is 12,50 while for the group of students given treatment (experimental group) is 15,15, meaning that there is an increase in test results againts the experimental group at 45%, (4) there is an increase in the observations of the discipline attitude from the control group compared to the experimental group at 35 %, (5) there is an increase in the observations of the discipline attitudes of the control group compared to the experimental group at 55%. Based on the above analysis it can be cocluded that the circuit training learning model can improve physical fitness and cultivate honesty, discipline and cooperattion in students of Elementary School.